Prognostic value of heart failure hospitalization in transthyretin cardiac amyloidosis: an international cohort study - Laenens, Dorien; Debonnaire, Philippe; De Smet, Maarten A. J.; Pinto, Fausto; Brito, Dulce; Droogmans, Steven; Verbrugge, Frederik H.; Donal, Erwan; Van de Veire; Nico; Bertrand, Philippe; Sia, Ching Hui; et al. (John Wiley & Sons, 2026)
Introduction
Data on the impact of a heart failure hospitalization (HFH) on outcome in patients with transthyretin cardiac amyloidosis (TTR-CA) are scarce, although it remains a frequent adverse event. To assess the characteristics of patients with HFH in a real-world TTR-CA population, the occurrence of HFH, and the prognosis thereafter.
Methods
Data were collected from a multicentre TTR-CA registry and patients were dichotomized according to the occurrence of at least one HFH. Landmark analysis at the 1-year follow-up and Cox regression analysis with HFH as a time-dependent covariate were performed to assess the impact of HFH on all-cause mortality.
Results
Overall, 654 patients were included [median age 78 (64, 83) years, 70.5% male, 70.6% wild type]. During a median follow-up of 24 (11–45) months, 141 (22%) patients experienced at least one HFH and 170 (26%) patients died. Patients with a HFH were older (82 vs 76 years, P < .001), had more wild-type TTR-CA [126 (89.4%) vs 336 (65.5%), P < .001], were more symptomatic [New York Heart Association Class II–IV 119 (86.9%) vs 279 (62%), P < .001], had higher National Amyloidosis Centre (NAC) disease stage, were less treated with disease-modifying therapy [45 (31.9%) vs 247 (47.4%), P = .001], had more co-morbidities and showed signs of more advanced disease by echocardiography. At the 1-year time point, patients with HFH had significant worse overall survival (log-rank χ² 37.673, P < .001). At the univariable (HR 7.71, 95%CI 5.50, 10.82; P < .001) and multivariable analyses, HFH was associated with all-cause mortality and showed incremental value on top of clinical variables, biomarkers [estimated glomerular filtration rate in Model 1 (χ² 97.3; P < .001) and NAC disease stage in Model 2 (χ² 78.8; P < .001)] and echocardiographic parameters (left ventricular mass index + stroke volume index + significant valvular lesion in Model 3 (χ² 60.3; P < .001) and including E/e′ in Model 4 (χ² 43.4; P < .001)).
Conclusion
HFH is independently associated with all-cause mortality in patients with TTR-CA and has incremental value on top of established risk models.